The Effects of the Faranak Parent-child Mother Goose Program on the Development of Auditory and Vocalization Skills of Deaf and Hard-of-hearing Children Under Six Years Old - Hakimeh Sadeghikhah; Somayeh Sadat Sadati Firoozabadi; Tahereh Soleimanieh-Naeini; Guita Movallali (Journal of Rehabilitation, 2025)
Objective Hearing loss (HL) in children can lead to challenges in communication, including delays in verbal and language development. Early intervention should focus on minimizing the negative impact of HL, with particular attention to fostering auditory and social communication skills. Faranak Parent-Child Mother Goose Program (P-CMGP), the Persian-language adaptation of P-CMGP, is used to develop these skills through effective parent-child relationships. This study assessed the effect of the Faranak P-CMGP on the development of auditory and vocalization skills of children who were deaf and hard-of-hearing (DHH) under six years old. Materials & Methods In this quasi-experimental study, with pre-test, post-test and follow-up, subjects were recruited from two early intervention centers for DHH children and their families in two cities of Bushehr Province, Iran. They were selected through a convenience sampling method and divided randomly into two groups, an intervention group and a control group. Overall, 53 DHH children with their mothers (27 in the intervention group and 26 in the control group) were included in this study. The intervention group participated in 30 weekly sessions (one-hour duration) of Faranak P-CMGP. The Persian version of the questionnaires including Purdy Auditory Behavior in Everyday Life (ABEL) and Kishon-Rabin Production of Infant Scale Evaluation (PRISE) were used to measure the development of auditory and vocalization skills. Results Statistically significant differences were found in the mean scores of the development of auditory and vocalization skills between the children of the intervention and control groups, in favor of the intervention group (P<0.001, in both instances). The intervention led to significant improvements in the auditory skill development of DHH children through three factors: auditory-oral skills, auditory awareness, and conversational/social skills, as well as in vocalization skill development (P<0.001 in all instances) in the post-test and follow-up. Based on the Eta squared coefficient, 30% and 32% of the changes between the scores of the development of auditory and vocalization skills of DHH children in the two groups may be attributed to the intervention. Conclusion The results demonstrated statistically significant and positive effect of the Faranak P-CMGP on the development of auditory and vocalization skills of DHH children. Considering the remarkable effect size obtained from Faranak P-CMGP and its easy application, this program can be a valuable addition to early intervention and rehabilitation efforts for DHH children. It has the potential to significantly develop the auditory awareness and auditory-oral skills of children and enhance mother-child relationships.